2016
DOI: 10.1155/2016/9432493
|View full text |Cite
|
Sign up to set email alerts
|

The Implications of Tobacco Smoking on Acute Postoperative Pain: A Prospective Observational Study

Abstract: Background. The clinical importance of cigarette smoking on acute postoperative pain perception is not fully understood. Methods. To determine whether smokers who underwent major surgery need more postoperative opiate than do nonsmokers. We prospectively enrolled 407 male and 441 female participants who underwent in-hospital surgery. Current-smokers were compared with nonsmokers and past-smokers about opiate use during the first 72 h after surgery. Results. A greater proportion of males had more smoking histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 23 publications
4
32
0
Order By: Relevance
“…One study revealed that current smokers required more morphine than non-smokers and past smokers during the 72 hours after other types of surgery. 12 However, the potential mechanisms of the interaction between smoking and acute postoperative pain are complex and not fully understood. 13 …”
Section: Discussionmentioning
confidence: 99%
“…One study revealed that current smokers required more morphine than non-smokers and past smokers during the 72 hours after other types of surgery. 12 However, the potential mechanisms of the interaction between smoking and acute postoperative pain are complex and not fully understood. 13 …”
Section: Discussionmentioning
confidence: 99%
“…They found that male current smokers required more opioid analgesia during the first 72 hours after surgery than the other 2 groups. 9 In addition, they also reported higher pain intensity scores on postoperative day (POD) 1. Patients undergoing elective fusion surgery are required to cease nicotine use prior to scheduling surgery.…”
Section: Tobacco Usementioning
confidence: 99%
“…A common finding in the literature is that current and previous tobacco use is associated with the risk of intense acute pain and persistent opioid use. 25,26 Smoking may be an important modifiable risk factor for pain intensity and opioid use after surgery. 27 The Opioid Risk Tool, which can be easily sourced on the Internet, 28 is a questionnaire that is usually used to assess an adult's propensity to develop an opioid use disorder in the setting of chronic pain.…”
Section: Recommendations and Summary Of Evidencementioning
confidence: 99%